A CARE-compliant article: a case of retrograde intussusception with Uncut-Roux-en-Y anastomosis after radical total gastrectomy. Issue 48 (December 2017) - Zhou, Youxin; Wang, Fengfeng; JI, Yong; Lv, Jian
Abstract: Rationale: Postoperative intussusception is an unusual clinical entity and is rarely encountered as a complication following gastrectomy, especially radical total gastrectomy. Patient concerns: A 74-year-old woman was admitted to our hospital with complaints of melena and hematemesis. And the endoscopic biopsy confirmed the poorly differentiated adenocarcinoma of the stomach. Radical total gastrectomy with Uncut Roux-en-Y reconstruction was performed. On the third postoperative day (POD3), the patient complained of paroxysmal pain around the umbilicus, accompanied by nausea and vomiting. Diagnosis: Retrograde intussusceptions after radical total gastrectomy with Uncut Roux-en-Y reconstruction based on exploratory laparotomy. Interventions: On POD4, the abdominal computed tomography (CT) showed small bowel dilatation and fluid accumulation in the upper abdominal cavity, as well as a small mass of soft tissue on the left side of the pelvis. Small bowel obstruction was considered, and exploratory laparotomy was performed. Retrograde intussusception started just below the jejunojejunal anastomosis with possible organic lesions, which was subsequently removed. Outcomes: The patient recovered well and was discharged 15 days after the second operation. Lessons: This case report was written for 3 purposes: to increase awareness of this complication after radical total gastrectomy with Uncut-Roux-en-Y reconstruction; to emphasize early diagnosis through clinical manifestation, physical examination, and auxiliary examination with abdominal CT; and lastly, to emphasize that a reasonable surgical procedure should be performed immediately after diagnosis.